Improvement of Exercise Ability and Liver Protection in Oxidative Stress-induced Mice by Lactiplantibacillus plantarum CQPC03 - Bo HE; Xin ZHAO; Xiaohong TAN; Kai MA; Caifeng LI (Shipin gongye ke-ji)
This study investigated the effects of a newly discovered lactic acid bacterium, Lactiplantibacillus plantarum CQPC03 (LP-CQPC03), on enhancing the exercise capacity of mice under oxidative stress and elucidated the underlying mechanisms. The oxidative stress model of mice was induced by D-galactose. Through running time, swimming endurance, blood biochemical indexes, histopathological changes, mRNA expression of gastritis muscle and liver tissue, and microbial composition of intestinal contents of mice, LP-CQPC03 was used to explore the improvement of exercise ability and liver protection of mice damaged by oxidative stress. The results showed that after administration of LP-CQPC03 (dose 1.5×109 CFU/kg BW), the running time and swimming endurance of mice with oxidative stress were significantly extended (P<0.05), and serum lactic acid, blood urea nitrogen (BUN) and creatine kinase (CK) concentrations decreased significantly (P<0.05), while muscle glycogen (MG) and hepatic glycogen (HG) levels increased significantly (P<0.05). Histopathological analysis indicated that LP-CQPC03 mitigated oxidative stress damage in the liver tissues of the mice. Further analysis showed that compared with model group, LP-CQPC03 could significantly (P<0.05) up-regulate expression of adenylate activated protein kinase (AMPK), peroxisome proliferator-activated receptor γ coactivator 1-α (PGC-1α), superoxide dismutase 2 (SOD2) and glutathione peroxidase 1 (GPx1) mRNA in liver and gastrocnemius muscle of oxidative stress mice. In addition, LP-CQPC03 also increased the abundance of Firmicutes, Lactobacillus and Bifidobacteria in the intestinal tract of mice under oxidative stress, while decreasing the expression of Bacteroidetes. In summary, LP-CQPC03 can not only improve the oxidative stress state of mice, but also significantly enhance their exercise ability, and the effect is better than that of vitamin C (150 mg/kg BW).